ANALISIS PENGARUH EKSPOR DAN IMPOR MIGAS - NON MIGAS TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2015- 2022 - Efri Rahmadhana (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2023)
This research aims to determine the influence of oil and gas and non-oil and gas exports on Indonesia's economic growth. Data taken from the Central Statistics Agency and the Ministry of Trade (Kemendag) in the form of quarterly time series data for the period 2015 - 2022. Analysis uses multiple linear regression with Eviews-12. Oil and gas exports have a negative and significant influence on Indonesia's economic growth in 2015-2022. Non-oil and gas exports have a positive but not significant influence on Indonesia's economic growth in 2015-2022. Oil and gas imports have a positive but not significant influence on Indonesia's economic growth in 2015-2022. Non-oil and gas imports have a positive but not significant influence on Indonesia's economic growth in 2015-2022. Taken together, oil and gas-non-oil and gas import exports have a significant influence on Indonesia's economic growth in 2015-2022 Keywords: Oil and Gas Exports, Non-Oil and Gas, Oil and Gas Imports, Non-Oil and Gas, Economic Growth.